Pengaruh Kepemilikan Institusional, Kepemilikan Manajerial, dan Kepemilikan Publik Terhadap Integritas Laporan Keuangan dengan Peran Komite Audit Sebagai Variabel Moderasi - Hana Alifah Nugraha; Susi Dwi Mulyani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to test and analyze the effect of institutional ownership, managerial ownership, and public ownership on the integrity of financial statements with the role of the audit committee as a moderating variable. The data used is secondary data obtained from financial reports and annual reports of food and beverage sub-sector companies listed on the IDX during the 2021-2023 period. The sample of this study was selected using purposive sampling technique, so that a total of 255 samples were obtained. Data analysis was carried out using multiple linear regression through the Eviews 12 application. The results showed that institutional ownership has a positive effect on the integrity of financial statements, while managerial ownership and public ownership have no effect on the integrity of financial statements. The role of the audit committee as a moderating variable can strengthen the positive effect of public ownership on the integrity of financial statements, while the role of the audit committee does not succeed in strengthening the effect of institutional ownership and managerial ownership on the integrity of financial statements.